Bioconversion of D-glucose into D-glucosone by Glucose 2-oxidase from Coriolus versicolor at Moderate Pressures - Karmali, Amin (2013)
Glucose 2-oxidase (pyranose oxidase, pyranose: oxygen-2-oxidoreductase, EC 1.1.3.10) from Coriolus versicolor catalyses the oxidation of D-glucose at carbon 2 in the presence of molecular O(2) producing D-glucosone (2-keto-glucose and D-arabino-2-hexosulose) and H(2)O(2). It was used to convert D-glucose into D-glucosone at moderate pressures (i.e. up to 150 bar) with compressed air in a modified commercial batch reactor. Several parameters affecting biocatalysis at moderate pressures were investigated as follows: pressure, [enzyme], [glucose], pH, temperature, nature of fluid and the presence of catalase. Glucose 2-oxidase was purified by immobilized metal affinity chromatography on epoxy-activated Sepharose 6B-IDA-Cu(II) column at pH 6.0. The rate of bioconversion of D-glucose increased with the pressure since an increase in the pressure with compressed air resulted in higher rates of conversion. On the other hand, the presence of catalase increased the rate of reaction which strongly suggests that H(2)O(2) acted as inhibitor for this reaction. The rate of bioconversion of D-glucose by glucose 2-oxidase in the presence of either nitrogen or supercritical CO(2) at 110 bar was very low compared with the use of compressed air at the same pressure. The optimum temperature (55 degrees C) and pH (5.0) of D-glucose bioconversion as well as kinetic parameters for this enzyme were determined under moderate pressure. The activation energy (E(a)) was 32.08 kJmol(-1) and kinetic parameters (V(max), K(m), K(cat) and K(cat)/K(m)) for this bioconversion were 8.8 Umg(-1) protein, 2.95 mM, 30.81 s(-1) and 10,444.06 s(-1)M(-1), respectively. The biomass of C. versicolor as well as the cell-free extract containing glucose 2-oxidase activity were also useful for bioconversion of D-glucose at moderate pressures. The enzyme was apparently stable at moderate pressures since such pressures did not affect significantly the enzyme activity.